Babesia microti Confers Macrophage-Based Cross-Protective Immunity Against Murine Malaria - Efstratiou, Artemis; Galon, Eloiza May S.; Wang, Guanbo; Umeda, Kousuke; Kondoh, Daisuke; Terkawi, Mohamad Alaa; Kume, Aiko; Liu, Mingming; Ringo, Aaron Edmond; Guo, Huanping; Gao, Yang; Lee, Seung-Hun; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Malaria and babesiosis, the two primary intraerythrocytic protozoan diseases of humans, have been reported in multiple cases of co-infection in endemic regions. As the geographic range and incidence of arthropod-borne infectious diseases is being affected by climate change, co-infection cases with Plasmodium and Babesia are likely to increase. The two parasites have been used in experimental settings, where prior infection with Babesia microti has been shown to protect against fatal malarial infections in mice and primates. However, the immunological mechanisms behind such phenomena of cross-protection remain unknown. Here, we investigated the effect of a primary B. microti infection on the outcome of a lethal P. chabaudi challenge infection using a murine model. Simultaneous infection with both pathogens led to high mortality rates in immunocompetent BALB/c mice, similar to control mice infected with P. chabaudi alone. On the other hand, mice with various stages of B. microti primary infection were thoroughly immune to a subsequent P. chabaudi challenge. Protected mice exhibited decreased levels of serum antibodies and pro-inflammatory cytokines during early stages of challenge infection. Mice repeatedly immunized with dead B. microti quickly succumbed to P. chabaudi infection, despite induction of high antibody responses. Notably, cross-protection was observed in mice lacking functional B and T lymphocytes. When the role of other innate immune effector cells was examined, NK cell-depleted mice with chronic B. microti infection were also found to be protected against P. chabaudi. Conversely, in vivo macrophage depletion rendered the mice vulnerable to P. chabaudi. The above results show that the mechanism of cross-protection conferred by B. microti against P. chabaudi is innate immunity-based, and suggest that it relies predominantly upon the function of macrophages. Further research is needed for elucidating the malaria-suppressing effects of babesiosis, with a vision towards development of novel tools to control malaria.